Barack Obama and The Daily Show's comic critique of whiteness: the intersection of popular and political discourse - Purtle, Stephanie M. (Kansas State University, 2009)
The 2008 presidential campaign controversy surrounding Rev. Jeremiah Wright’s sermons had the potential to derail Barack Obama’s candidacy. At the heart of the controversy was race, specifically Whiteness. Obama’s speech “A More Perfect Union” is perhaps one of the most significant political speeches addressing race to date, and warrants analysis. However, Barry Brummett’s book Rhetorical Dimensions of Popular Culture (1991) argues the critic should not be limited to discrete traditional texts, rather should be able to break outside such traditional speaker-focused boundaries. Brummett’s mosaic model allows an exploration of the intersection between popular and political rhetoric of Obama and The Daily Show. I will argue from the intersection we see the emergence of the comic frame as a homology that links the disparate texts of Obama and TDS. I will argue the reason the comic frame emerges from the texts is because there is a societal mandate for the comic frame. Thus, I will ultimately argue the mandate for the comic frame can be better understood as a social movement. However, it is a movement comprised of numerous individual movements, and warrants a new term: meta-movement. Obama and TDS are not leaders of this meta-movement, but instead should be seen as contributors. Brummett urges the critic to consider “the political or ideological interests served by ordering a rhetorical transaction in a certain way” (1991, p. 98). I will argue constructing the rhetoric of Obama and TDS with the comic frame serves the ideological interests of those who are fighting for social justice and working to subvert Whiteness. Thus, I have named the meta-movement to which Obama and TDS contribute a critical optimist movement, because the comic frame provides the tools to be critical of hegemony while ultimately reinforcing the optimistic assumption of the comic frame: all humans are ultimately both flawed and good.
Keywords: Barack Obama; The Daily Show with Jon Stewart; Barry Brummett; Whiteness; Comic frame; Social movements; Speech Communication (0459)